The molecular prevalence, distribution and risk factors associated with Babesia bigemina infection in Peninsular Malaysia - David, Ola-Fadunsin Shola; Sharma, Reuben Sunil Kumar; Abdullah, Donea Abdulrazak; Gimba, Fufa Ido; Abdullah, Faez Firdaus Jesse; Abdullah Sani, Rehana (Elsevier, 2021)
Babesia bigemina is a tick-borne protozoan that affects cattle in almost all regions of the world. Despite its importance, there is no report of its prevalence in cattle using molecular detection methods in Peninsular Malaysia. This study describes the prevalence, distribution, and risk factors associated with B. bigemina infection using molecular diagnostic methods. Also, the species of ticks infesting cattle and the attitude of cattle farmers towards tick control in Peninsular Malaysia were studied. Blood samples were collected from 1045 cattle from 43 herds throughout the country, and were subjected to molecular studies to detect B. bigemina. Tick samples for entomological studies were also collected and identified. Epidemiological information of each cattle and farm were obtained using a well-structured questionnaire containing open-ended and closed-ended questions. Data were statistically analyzed using Univariate and Multivariate models. The 211-base pair of AMA-1 gene of B. bigemina was amplified and confirmed in 30.5 % (319/1045; 95 % CI = 27.8–33.4) of the sampled population, with the haemoprotozoan detected in all the sampled herds. Breed, age, physiological status, management type, rate of de-ticking, and closeness to human settlement were the risk factors significantly (p < 0.05) associated with the prevalence of B. bigemina in cattle. Rhipicephalus (Boophilus) microplus and Haemaphysalis bispinosa were the species of ticks collected from cattle, with the former been more prevalent. A large number of cattle farmers (12/43; 28 %) do not control ticks in their herds. The findings of this study will create baseline data on the epidemiology of the haemoprotozoan and control patterns of its tick vectors that will guide the government in enacting policies that will improve food security and the economy of the nation.